Lucius Tarius Rufus, primus inter Liburnos? - Demicheli, Dino (Array, 2014)
With this paper we would like to encircle all the epigraphical, archaeological and litrerary sources related to the consul, general and businessman Lucius Tarius Rufus and try to compare them mutually. Although we know a little on his life, there is a general opinion that he was probably from the area of Nedinum in Liburnia and played very important role in the first decades of the Empire. For his military achievements and friendship with Augustus, according to the Pliny's statement, he became very rich and purchased agricultural land in Picenum. From the archaeological sources we know that he produced wine that was stored in ceramic vessels with the stamps bearing his name. In the paper we will give all the major facts about his life, but also some new questions and assumptions related to his role in the connection between Rome and Liburnia.